2010
DOI: 10.1016/j.bpj.2010.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characterization of an Ensemble of Intramolecular i-Motifs Formed by the Human c-MYC NHE III1 P1 Promoter Mutant Sequence

Abstract: i-Motif-forming sequences are present in or near the regulatory regions of >40% of all genes, including known oncogenes. We report here the results of a biophysical characterization and computational study of an ensemble of intramolecular i-motifs that model the polypyrimidine sequence in the human c-MYC P1 promoter. Circular dichroism results demonstrate that the mutant sequence (5'-CTT TCC TAC CCTCCC TAC CCT AA-3') can adopt multiple "i-motif-like," classical i-motif, and single-stranded structures as a func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…The nonlinear regression fitting was done using CHASM data analysis program developed in our laboratory [24]. The ITC fitting procedures used here have been described previously [17,19,2527]. …”
Section: Methodsmentioning
confidence: 99%
“…The nonlinear regression fitting was done using CHASM data analysis program developed in our laboratory [24]. The ITC fitting procedures used here have been described previously [17,19,2527]. …”
Section: Methodsmentioning
confidence: 99%
“…It is well known that CD spectrum for a typical i‐motif DNA structure exhibits a positive peak at (or near) 286 nm followed by a negative peak at 265 nm while the B‐DNA like structure exhibits a positive peak at (or near) 275 nm and negative peak at 254 nm. [ ] Figure A shows the CD spectra of 4 μM 11Py in sodium cacodylate buffer at varied pH (4.5, 5.7 and 7.0), containing 100 mM NaCl. At acidic pH, the CD spectrum of 11Py showed signature peak of i‐motif formation .…”
Section: Resultsmentioning
confidence: 99%
“…Later, several proteins have been identified that could shift the pKa of the formation of i‐motif to a more basic value and hence, can stabilize the i‐motif structure at either near neutral or neutral pH . Recent reports suggest that molecular crowding environment raise the p K a value of cytosine at N3 position which can fold the (CCT) 8 triple repeat DNAs or C‐rich sequences located in promoter region of c‐myc at neutral pH into i‐motif structure . Zhao et al (2008) reported the formation of stable i‐motif structure using single‐walled carbon nanotubes as a mimicking agent …”
Section: Resultsmentioning
confidence: 99%
“…6 E). Thus, these results indicate that factors such as the superhelical density of the DNA, the binding of specific proteins, and macromolecular crowding conditions inside the cell could facilitate the formation of i-motif structures under physiological conditions (101,102).…”
Section: The I-motif Blocks Primer Extension By Dna Polymerasementioning
confidence: 96%